A further examination of managerial burnout : toward an integrated model - Lee, Raymond T. [Verfasser]; Ashforth, Blake E. [Verfasser] (My University, 1993)
"A model of managerial burnout was examined among 148 human service supervisors and managers. The findings suggest that emotional exhaustion plays a central mediating role in the burnout process. Social support and direct control were associated with exhaustion through role stress. Job and life satisfaction, and time spent with clients and subordinates were also related to exhaustion. In turn, exhaustion was related to depersonalization, professional commitment, and turnover intentions. An expected reciprocal relation between exhaustion and helplessness was not found, as the former had only a weak impact on the latter. Implications for stress coping are discussed." (author's abstract) ((en)) In dem Beitrag wird ein Modell untersucht, das das Burnout von Führungskräften erklären soll. Die Ergebnisse zeigen, dass die emotionalen Erschöpfung eine vermittelnde Rolle spielt. Damit verbunden sind wiederum folgende Einflussfaktoren: soziale Unterstützung, Kontrollmöglichkeiten, Arbeits- und Lebenszufriedenheit sowie die Zeit, welche für Kunden und Mitarbeiter verwandt wird. (IAB)
Keywords: G 1.2.2.2 Soziale Sicherungssysteme; G 2.3.1 Arbeitsteilung & -organisation; G 2.4.2 Lebenskonzepte, -stile, Werte; G 2.4 Sozialer Wandel; G 1.2.2.3 Beschäftigungsformen; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 2.4.4 Biografiegestaltung; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3 Wandel von Arbeit & Wirtschaft; Führungskraft; Burn-out-Syndrom; Soziale Unterstützung; Arbeitszufriedenheit; Zufriedenheit; Lebenssituation; Mitarbeiter; Soziale Beziehungen; Berufszufriedenheit; Stressbewältigung; Berufsproblem; Quantitative Angaben